Kinetics and Thermodynamics of β- Endosulfan Pesticide 2 Adsorptionin Jordan Valley Soils (Global Journal of Science Frontier Research, 2020)
Knowledge of the β-endosulfan adsorption characteristics of soil is necessary for predicting its mobility and fate in soil environments. To examine the characteristics of βendosulfan retention, sorption batch experiments were performed on three Xeropsamments soils having different properties. The sorption data were applied to various kinetics models. The results reveal that the tested models fitted the adsorption data in the order: first-order~modified Freundlich > parabolic diffusion >Elovich. The energy of activation (Ea) and enthalpy (ΔH#), entropy (ΔS#), and free energy of activation (ΔG#) related to β-endosulfan sorption were calculated using the Arrhenius equation. The activation energy (Ea) values (18.57 -38.18 kJ mol -1 ) and the positive ΔH# values characterize β-endosulfan adsorption process onto the sorbents studied as physisorption with an endothermic nature. The negative values of ΔS # (-23-17 J mol -1 ) obtained in this study suggest that the β-endosulfan sorption process involves an associative mechanism.
Keywords: equilibrium isotherm models• kinetic models • associative mechanism• physisorption